Pengaruh Influencer Marketing Terhadap Keputusan Pembelian Sepatu Geoff Max Di Kota Pontianak Dengan Customer Perceived Value Sebagai Mediasi - Ilpan; Mursalin, Adi; Hendharsa, Angga (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2025)
This study aims to analyze the influence of Influencer Marketing on purchasing decisions of Geoff Max shoes in Pontianak City with Customer Perceived Value as a mediating variable. Using an associative quantitative method with purposive sampling, this study involved 100 respondents and was analyzed through SEM-PLS 3.0 using SmartPLS. The results show that Influencer Marketing has a significant effect on Purchasing Decisions (p-value 0.004 <0.05) and increases Customer Perceived Value (p-value 0.000 <0.005). Customer Perceived Value also has a positive impact on Purchasing Decisions (p-value 0.000 <0.05) and acts as a mediating variable (p-value 0.000 <0.05). This finding confirms that the success of Influencer Marketing depends not only on popularity, but also on its ability to form positive perceptions of product value, which drives purchasing decisions